EFL Pre-service Teachers' Perceptions towards Digital Academic Reading - Umy Hamidah; Dyah Sunggingwati; Effendi Limbong (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2024)
E-learning has increasingly focused on improving digital reading skills and developing an efficient digital reading mode as digital reading becomes more prevalent. This study explored students' perceptions of digital academic reading in e-learning, focusing on enhancing digital reading competency and establishing an effective reading mode. Using a qualitative research approach defined by Creswell (2014), the study targeted 2019 A English Department students at Mulawarman University. From a questionnaire, nine participants were selected for interviews. Findings indicated that all participants had positive attitudes toward digital academic reading, with an average questionnaire score of 80.6. Most preferred digital reading over printed materials, particularly in the EFL (English as a Foreign Language) context at higher education levels. The advantages of digital reading included accessibility, practicality, versatility, portability, lighting independence, and reduced sleepiness. However, disadvantages such as reliance on the internet and battery life, notification distractions, and eye strain were noted. Despite some drawbacks, the study concluded that digital academic reading was highly effective for higher-education EFL students. These insights contributed to developing more efficient digital reading strategies in e-learning environments.